ANALISIS DETERMINAN KEJADIAN GIZI KURANG PADA BALITA - Andi Hardianti; Supriyatni Kartadarma; Zaida Mauludiyah; Desy Dwi Cahyani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The nutritional status of infants and children is one of the key indicators for assessing growth and development in early life. According to the World Health Organization (WHO), millions of children under the age of five still suffer from growth and developmental disorders due to various health and nutritional problems. The purpose of this study was to analyze the determinants of malnutrition among toddlers. A cross-sectional study design was used in this research. The study was conducted in the service area of the Margorejo Community Health Center (Puskesmas). The sample consisted of 85 respondents. Simple random sampling was used for data collection. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed an association between a history of low birth weight (p-value: 0.018) and exclusive breastfeeding (p-value: 0.000) with the incidence of undernutrition in toddlers. It is recommended that community health centers evaluate and provide support to toddlers experiencing malnutrition and improve their services, such as educating parents on the importance of mothers attending Posyandu to monitor their children’s nutritional status.Keywords: Toddlers, Low Birth Weight, Malnutrition.